The effect of sodium bicarbonate ingestion on plasma lactate, bicarbonate and the anaerobic performance in female 400-meter runners - Eftekhari, E.; Poormohammadi, F. (International Journal of Applied Exercise Physiology, 2019)
Sodium bicarbonate (BICA) supplement by buffering capacity and delaying the metabolic acidosis, may improve exercise capacity, but there are controversial results could be related to the various type and intensity of exercises. The purpose of this study was to investigate the effect of BICA ingestion on blood pH, bicarbonate (HCO3-), lactate (BLa), and anaerobic capacity in the female 400-meter runners. This research method was semi-experimental. 17 female runners (age= 20-27 yrs., BMI= 20.40 ± 1.41 Kg.m-2) participated in this research. The protocol was held in two sessions with one-week rest time between sessions. The blood sampling was collected to evaluate serum pH, HCO3-, and BLa, which was done before and after 400-meter running (Pre1-Post1) in the first session (Control), and three times [before supplementation (Pre*1), 70-minute after supplementation (Post*1), and 2-minute after test (Post*2)] in the second session (BICA). The running time was recorded in each session. The results showed 400-meter running cause significant decrease in serum pH (t= 59.5, sig=0.01*), HCO3 (t= 17.91, sig=0.01*), and increase in serum BLa (t= 50.19, sig=0.01*) in control group. After supplementation (BICA) pH, HCO3 and BLa increase from rest (Post*1) and after 400-meter running pH, HCO3 decreased and BLa increased (Post*2) (p<0.05). The comparing Post*2 with Post1 showed BICA caused significantly increase pH, and BLa and decrease the 400.meter running time (p<0.05). This research recommends this dosage of BICA supplementation could be effective to reach a better record in 400-meter running that may have related to metabolic acidosis.